Choice Mode Study Between Motorcycle and "Microlet" Public Transportation as Tripwork - Azis, Arief Akbar; Rakhmatulloh, Anita Ratnasari (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2012)
Semarang is one of Indonesiaâ€™s largest cities facing high demand for mobility especially commuter trips toÂ  the places of work. On the one hand, supply of good public transport is lacking in both number and service coverage, on the other hand, demand continues to increase. People will tend to chose modes which are affordable, reliable, flexible and convenient. Motorcycles was the answer. The study examined the utility value of motorcycles, and at what level would they be willing to keep shift to public transports.